2010
DOI: 10.2174/1874473711003010003
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of Laboratory-Based Studies Examining the Relationships of Social Anxiety and Alcohol Intake

Abstract: Research has revealed inconsistencies regarding the relationship between social anxiety and alcohol use. The goal of the current review is to examine lab-based studies that have been conducted in an attempt to help disentangle the social anxiety - alcohol link. Specifically, this review focuses on the most prominent theories present in this area of research, namely, the Tension Reduction Theory, the Stress-Response Dampening Model, the Self-Awareness Model, the Attention Allocation Model, and the Appraisal-Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 128 publications
3
33
0
Order By: Relevance
“…There are negative short-term overspills via hangovers, and overspills on multiple timescales via health/social harms. More positively, it is often suggested that alcohol improves sociability, with real-world interactions reported to be more agreeable with alcohol (aan het Rot et al, 2008), laboratory studies showing a reduction in social anxiety (Battista et al, 2010), and qualitative research describing 'anticipatory pleasures' and 'retrospective bonding' around drinking (Brown & Gregg, 2012). However, the scale, dose-response and timing of some of these overspill effects is unclear.…”
Section: Subjective Wellbeing Methodsmentioning
confidence: 99%
“…There are negative short-term overspills via hangovers, and overspills on multiple timescales via health/social harms. More positively, it is often suggested that alcohol improves sociability, with real-world interactions reported to be more agreeable with alcohol (aan het Rot et al, 2008), laboratory studies showing a reduction in social anxiety (Battista et al, 2010), and qualitative research describing 'anticipatory pleasures' and 'retrospective bonding' around drinking (Brown & Gregg, 2012). However, the scale, dose-response and timing of some of these overspill effects is unclear.…”
Section: Subjective Wellbeing Methodsmentioning
confidence: 99%
“…Previous experimental research examining the effect of alcohol on state social anxiety has yielded inconsistent findings (e.g., see Battista et al, 2010). The primary purpose of the current experiment was to examine whether SRD specific to state social anxiety varies as a function of the type of social context (i.e., a speech or a conversation) and measurement point (i.e., two pre-stressor anticipatory, during stressor, and post-stressor SUDS ratings).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it stands to reason that SRD effects would be observed in a sample of socially anxious drinkers, as SRD is hypothesized to be stronger for individuals elevated in certain trait-like variables that make these anxiolytic effects particularly reinforcing (e.g. Battista et al, 2010;Sher & Levenson, 1982). Though previous research that provided full or partial support for SRD include both non-clinical samples of undergraduates (Balodis et al, 2011;de Boer et al, 1993;Sayette et al, 1992;Wilson & Abrams, 1977) and clinical samples of socially anxious individuals and trait social anxiety did not moderate the effects in the present study, it could be that alcohol operates differently among those for whom the anxiolytic effects of alcohol would be most reinforcing.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations